COMPLICATION OF CORTICOSTEROID INJECTION: RUPTURE OF PLANTAR FASCIA - Nadeem Akbar Baloch; Shahzaib Riaz Baloch; Mohammad Sohail Rafi; Mohammad Idrees Shah; Faateh Siddiq (ziauddin University, 2019)
Introduction: A series of 550 patients with a clinical diagnosis of plantar fascitis. All patients were initially given a conservative trial with anti-inflammatory medications along with resting and icing and rest. 280 patients of planter fascitis got relieved by such conservative management. Only 270 patients received corticosteroid injections and 37 of them were diagnosed with planter fascia rupture post injection. The Diagnosis of the rupture was mostly clinical which was assessed by windlass stretch test by dorsiflexion of the ankle and first toe. In patients who are diabetic the chances of rupture also increases. Treatment following rupture included supportive shoes, orthoses, and time. Methods: All patients with clinical diagnosis of PF who came to Dr. Ziauddin Hospital out-patient department from 2012 to 2016 were taken into our study after consent. Only those patients were given CI that reappeared to the Outpatient with similar or worsening of symptoms. 4 out of the 37 patients in whom the clinical assessment was inconclusive MRI were done which showed attenuation of the plantar fascia. From these observations and data, the author concluded that PFR had occurred. Results: Out of 270 patients only 37 patients (13.7%) were diagnosed with plantar fascia rupture. With increase in BMI the chances rupture increases. The majority had resolution of their new symptoms, but they often took up to 6 months to reoccur. In the remainder, there were persisting symptoms. Conclusion: Corticosteroid injections, although helpful in the treatment of plantar fascitis, appear to predispose to plantar fascia rupture.